Operando X-ray scattering study of thermoelectric β-Zn(4)Sb(3) - Rabøl Jørgensen, Lasse (International Union of Crystallography, 2020)

(untitled) (IUCrJ)
The application of thermoelectrics for energy harvesting depends strongly on operational reliability and it is therefore desirable to investigate the structural integrity of materials under operating conditions. We have developed an operando setup capable of simultaneously measuring X-ray scattering data and electrical resistance on pellets subjected to electrical current. Here, operando investigations of β-Zn(4)Sb(3) are reported at current densities of 0.5, 1.14 and 2.3 A mm(−2). At 0.5 A mm(−2) no sample decomposition is observed, but Rietveld refinements reveal increased zinc occupancy from the anode to the cathode demonstrating zinc migration under applied current. At 1.14 A mm(−2) β-Zn(4)Sb(3) decomposes into ZnSb, but pair distribution function analysis shows that Zn(2)Sb(2) units are preserved during the decomposition. This identifies the mobile zinc in β-Zn(4)Sb(3) as the linkers between the Zn(2)Sb(2) units. At 2.3 A mm(−2) severe Joule heating triggers transition into the γ-Zn(4)Sb(3) phase, which eventually decomposes into ZnSb, demonstrating Zn ion mobility also in γ-Zn(4)Sb(3) under electrical current.